Improved proton conduction of sulfonated poly (ether ether ketone) membrane by sulfonated covalent organic framework nanosheets. (29th July 2021) - Yin, Zhuoyu; Geng, Haobo; Yang, Pengfei; Shi, Benbing; Fan, Chunyang; Peng, Quan; Wu, Hong; Jiang, Zhongyi
Abstract: A type of sulfonated covalent organic framework nanosheets (TpPa-SO3 H) was synthesized via interfacial polymerization and incorporated into sulfonated poly (ether ether ketone) (SPEEK) matrix to prepare proton exchange membranes (PEMs). The densely and orderly arranged sulfonic acid groups in the rigid skeleton of the TpPa-SO3 H nanosheets, together with their high-aspect-ratio and well-defined porous structure provide proton-conducting highways in the membrane. The doping of TpPa-SO3 H nanosheets led to an increased ion exchange capacity up to 2.34 mmol g −1 but a 2-folds reduced swelling ratio, remarkably mitigating the trade-off between high IEC and excessive swelling ratio. Based on the high IEC and orderly arranged proton-conducting sites, the SPEEK/TpPa–SO3 H–5 membrane exhibited the maximum proton conductivity of 0.346 S cm −1  at 80 °C, 1.91-folds higher than the pristine SPEEK membrane. The mechanical strength of the composite membrane was also improved by 2.05-folds–74.5 MPa. The single H2 /O2 fuel cell using the SPEEK/TpPa–SO3 H–5 membrane presented favorable performance with an open voltage of 1.01 V and a power density of 86.54 mW cm −2 . Graphical abstract: Image 1 Highlights: COF nanosheets with intrinsic proton conductivity are blended with SPEEK matrix. Densely and orderly arranged –SO3 H on COF nanosheets offer proton-conducting pathways. Proton conductivity and mechanical strength of hybrid membranes are enhanced.